2015
DOI: 10.1088/1748-6041/11/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of hard and soft tissue healing in the oral cavity by a single transmucosal injection of fluvastatin-impregnated poly (lactic-co-glycolic acid) microspheres. An in vitro and rodent in vivo study

Abstract: Antihyperlipidemic drug statins reportedly promote both bone formation and soft tissue healing. We examined the effect of sustained-release, fluvastatin-impregnated poly(lactic-co-glycolic acid) (PLGA) microspheres on the promotion of bone and gingival healing at an extraction socket in vivo, and the effect of fluvastatin on epithelial cells and fibroblasts in vitro. The maxillary right first molar was extracted in rats, then one of the following was immediately injected, as a single dose, into the gingivobucc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…These include nanostructured lipid carriers, 6 solid dispersion, 7 nanoparticles, 8 , 9 and microspheres. 10 In the past few years, the use of particle size reduction method to form stable nanoparticles has proved an effective strategy to solve this thorny problem. Nanoscale suspensions can be defined as liquid dispersions consisting of solid drug nanoparticles, which are stabilized by polymers and/or surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…These include nanostructured lipid carriers, 6 solid dispersion, 7 nanoparticles, 8 , 9 and microspheres. 10 In the past few years, the use of particle size reduction method to form stable nanoparticles has proved an effective strategy to solve this thorny problem. Nanoscale suspensions can be defined as liquid dispersions consisting of solid drug nanoparticles, which are stabilized by polymers and/or surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…This DDS has been shown to release fluvastatin at a constant rate for >1 month. 35,36 The method of fabricating microcarriers in this study is referenced in these preceding studies with a modification in the impregnation procedure of drugs into PLGA. This is because fluvastatin is water soluble, but BD is water insoluble.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that there is evidence to suggest that statins, which have been safely used for treatment of hypercholesterolemia, enhance the biosynthesis of BMP-2 [ 42 ]. Other studies have reported the positive effects of statins on osteogenesis around implants and in tooth extraction sockets [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the systemic administration of simvastatin promoted bone formation around implants [ 21 ] and a topical application of fluvastatin led to bone formation around tibial titanium implants [ 22 ]. In addition, the injection of poly(lactic-co-glycolic) acid PLGA-fluvastatin microspheres promoted both bone formation and gingival soft tissue healing [ 23 , 24 ]. Jinno et al reported that atelo-collagen and alpha-tricalcium phosphate (α-TCP) as a carrier successfully promoted vertical bone formation on the parietal region [ 25 ].…”
Section: Introductionmentioning
confidence: 99%